2021
DOI: 10.1016/j.ijid.2020.10.103
|View full text |Cite
|
Sign up to set email alerts
|

Safety and immunogenicity of co-administration of meningococcal type A and measles–rubella vaccines with typhoid conjugate vaccine in children aged 15–23 months in Burkina Faso

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 20 publications
3
15
1
Order By: Relevance
“…A single dose of TCV demonstrated a robust antibody response in Burkinabe infants at nine months of age, including day 28 seroconversion in 87Á8% with GMT of 1203Á7 EU/mL. These results are consistent with previous studies of this vaccine (Jin et al, 2017;Kundu et al, 2020;Mohan et al, 2015;Shakya et al, 2019;Sirima et al, 2020) A study in Indian children ages 6 months to 2 years documented day 42 GMT of 1115 EU/mL (Kundu et al, 2020). A separate study in Indian children ages 24 months to 4 years found day 42 seroconversion in 97Á3% with a GMT of 1293 EU/mL (Mohan et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…A single dose of TCV demonstrated a robust antibody response in Burkinabe infants at nine months of age, including day 28 seroconversion in 87Á8% with GMT of 1203Á7 EU/mL. These results are consistent with previous studies of this vaccine (Jin et al, 2017;Kundu et al, 2020;Mohan et al, 2015;Shakya et al, 2019;Sirima et al, 2020) A study in Indian children ages 6 months to 2 years documented day 42 GMT of 1115 EU/mL (Kundu et al, 2020). A separate study in Indian children ages 24 months to 4 years found day 42 seroconversion in 97Á3% with a GMT of 1293 EU/mL (Mohan et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…A separate study in Indian children ages 24 months to 4 years found day 42 seroconversion in 97·3% with a GMT of 1293 EU/mL ( Mohan et al, 2015 ). In 15-month-old Burkinabe children, the day 28 seroconversion of 94–96% was higher than the current study with a GMT of 2757–3707 EU/mL ( Sirima et al, 2020 ). The higher responses in the 15-month-old children may reflect an enhanced immune response in children with more mature immune systems.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations